Caeca Microbial Variation in Broiler Chickens as a Result of Dietary Combinations Using Two Cereal Types, Supplementation of Crude Protein and Sodium Butyrate - Borda-Molina, Daniel; Mátis, Gábor; Mackei, Máté; Neogrády, Zsuzsanna; Huber, Korinna; Seifert, Jana; Camarinha-Silva, Amélia (Frontiers in Microbiology, 2021)
The intestinal microbiome can influence the efficiency and the health status of its host’s digestive system. Indigestible non-starch polysaccharides (NSP) serve as substrates for bacterial fermentation, resulting in short-chain fatty acids like butyrate. In broiler’s nutrition, dietary crude protein (CP) and butyrate’s presence is of particular interest for its impact on intestinal health and growth performance. In this study, we evaluated the effect on the microbial ecology of the ceca of dietary supplementations, varying the cereal type (maize and wheat), adequate levels of CP and supplementation of sodium butyrate on broiler chickens with 21 days. The overall structure of bacterial communities was statistically affected by cereal type, CP, and sodium butyrate (p = 0.001). Wheat in the diet promoted the presence of Lactobacillaceae, Bifidobacteriaceae and Bacteroides xylanisolvens, which can degrade complex carbohydrates. Maize positively affected the abundance of Bacteroides vulgatus. The addition of CP promoted the family Rikenellaceae, while sodium butyrate as feed supplement was positively related to the family Lachnospiraceae. Functional predictions showed an effect of the cereal type and a statistical significance across all supplementations and their corresponding interactions. The composition of diets affected the overall structure of broilers’ intestinal microbiota. The source of NSP as a substrate for bacterial fermentation had a stronger stimulus on bacterial communities than CP content or supplementation of butyrate.